Tiryns, Griechenland. Die Arbeiten der Jahre 2015 bis 2018 - Maran, Joseph; Papadimitriou, Alkestis; Birndorfer, Thomas; Khamnueva, Svetlana; Bork, Hans-Rudolf; Unkel, Ingmar; Kroll, Helmut (e-Forschungsberichte des DAI, 2019)
This report deals with recent research in the Northwestern Lower Town of Tiryns, built in the early 12th century BC as a new part of the site. It focuses on the cultural and social changes between the late Palatial Period and the older half of the Post-Palatial Period (c. 1220–1130 BC).